Kinetic Method for Spectrophotometric Determination of Iron(III) by its Catalytic Effect on the Reduction Reaction of Methyl Red with Potassium Pyrosulfite - FATHI, M.R.; POURREZA, N.; ABBASZADEH, S. (Asian Journal of Chemistry, 2010)
A kinetic spectrophotometric method for the determination of iron(III) is described. The method is based on the catalytic effect of iron(III) on the reduction reaction of methyl red by pyrosulfite. The reaction is followed spectrophoto-metrically by measuring the change in absorbance at 522 nm using a fixed time method (2.5 min). The effect of different parameters on the reaction was studied to obtain optimum conditions. The calibration curve was linear in the range of 0.4-2.0 μg mL-1 of iron(III) and the 3Sb detection limit was 0.07 μg mL-1. The method was successfully applied to the determination of iron(III) in an iron oral drop and clover plant.